EFEKTIVITAS PEMUNGUTAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN DONGGALA - Syawal, Muhammad (Katalogis, 2016)
This research aims at analyzing the effectiveness of tax collection  of non metallic minerals and rocks using a qualitative descriptive analysis. The concept used as a basis for analysis is an effectiveness standard proposed by Duncan namely Goals Achievement, Integration, and Adaptation. The number of informants in this study were 8 people. The results show that the tax collection system of non metal minerals and rocks was accomplished based on the regulation of Donggala District No. 1, 2011 on Local Taxes. The data were collected through observations, interviews, and documentations. The  approach technique of this analysis is to describe the meaning or significance of the problems, circumstances or situations that arise in the research object. The results show that the effectiveness of the tax collection system of non metallic minerals and rocks on with the indicator "Goals Achievement" viewed from the aspects: First; Tax Data gathering has not describe optimal results yet. Second; Realization of Tax Receipts always exceeds the target that indicates it has been effective. Third; Tax Deposit supervision, it is known that the mechanism of non metallic minerals and rocks tax payment is already running effective. Based on indicator of integration viewed from two aspects: First; Coordination between internal work units DPPKAD Donggala has not run properly. Similarly, cross-SKPD external coordination with the Department of Energy and Mineral Resources Donggala also has not run well. Secondly; Socialization to taxpayers already showed optimal results. Based on  adaptation indicator based on those two aspects: Tax collector resource,  the aspect of tax collection facility and tax collection Procedures .